2016
DOI: 10.1097/mrr.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between static posturography measures and specific cognitive domains in individuals with multiple sclerosis

Abstract: There are still limitations as to the understanding of the cognitive-postural control relationship in people with multiple sclerosis (PwMS). The aim of the current study' was to examine the relationship between cognition with measures of posturography in PwMS. The study was cross-sectional comprising 253 PwMS (162 women) with a mean age of 42.0 (SD=14.0). All participants completed a computerized cognitive test battery designed to evaluate multiple cognitive domains (Mindstreams; NeuroTrax) and static posturog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In limiting the number of tasks we were aware that MS patients have a limited stamina and fatigue which is an important confounding factor in balance measurements ( 1 ). Similar to previous studies that showed an association between impaired cognition/fatigue and impaired balance, based on data obtained from a part of the cohort, our remitting patients also showed signs of decreased mentation or moderate or severe fatigue as measured by the appropriate FS score of the EDSS ( 26 29 ). However, in this respect it is important to note that patients in this study did not state that the tasks were fatiguing.…”
Section: Discussionsupporting
confidence: 88%
“…In limiting the number of tasks we were aware that MS patients have a limited stamina and fatigue which is an important confounding factor in balance measurements ( 1 ). Similar to previous studies that showed an association between impaired cognition/fatigue and impaired balance, based on data obtained from a part of the cohort, our remitting patients also showed signs of decreased mentation or moderate or severe fatigue as measured by the appropriate FS score of the EDSS ( 26 29 ). However, in this respect it is important to note that patients in this study did not state that the tasks were fatiguing.…”
Section: Discussionsupporting
confidence: 88%